Nowe możliwości obrazowania siatkówki ludzkiego oka in vivo z zastosowaniem optyki adaptywnej The new possibilities of the in vivo retinal imaging with the use of adaptive optics - Ulińska, Magdalena; Zaleska-Żmijewska, Anna; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Knowledge of retinal anatomy has been closely related to histology studies. The analysis of retinal microstructures, including photoreceptor cells, and capillaries used to be limited due to the relatively poor resolution of retinal imaging techniques. Imaging modalities capable of detecting and monitoring pathological variations of retinal microstructures were only developed in late 20th century and 21st century. There is still a need for sensitive and accurate diagnostic tools, and a growing number of new diagnostic tools have become available in ophthalmology. In the current paper, we discuss a new diagnostic device rtx1, based on adaptive optics technology intended for an improved visualization of retinal microstructures, photoreceptors, and capillaries. We have reviewed adaptive optics technology for retinal imaging, both in healthy individuals and in patients with different retinal and systemic vascular diseases.